Iowa Gambling Task with non-clinical participants: effects of using real + virtual cards and additional trials - Overman, William H.; Pierce, Allison (Frontiers in Psychology, 2013)
Performance on the Iowa Gambling Task (IGT) in clinical populations can be interpreted only in relation to established base line performance in normal populations. As in all comparisons of assessment tools, the normal base line must reflect performance under conditions in which subjects can function at their best levels. In this review, we show that a number of variables enhance IGT performance in non-clinical participants. First, optimal performance is produced by having participants turn over real cards while viewing virtual cards on a computer screen. The use of only virtual cards results in significantly lower performance than the combination of real + virtual cards. Secondly, administration of more than 100 trials also enhances performance. When using the real/virtual card procedure, performance is shown to significantly increase from early adolescence through young adulthood. Under these conditions young (mean age 19 years) and older (mean age 59 years) adults perform equally. Females, as a group, score lower than males because females tend to choose cards from high-frequency-of-gain Deck B. Groups of females with high or low gonadal hormones perform equally. Concurrent tasks, e.g., presentation of aromas, decrease performance in males. Age and gender effects are discussed in terms of a dynamic between testosterone and orbital prefrontal cortex.